Virtual School Startups: Founder Processes in American K-12 Public Virtual Schools - Taylor, Brett Drushal; McNair, Delores E. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
Traditional school districts do not have a lot of experience with virtual schools and have lost students to state and charter virtual schools. To retain students and offer alternative learning opportunities, more public districts are starting their own virtual schools. This study was an examination of foundational processes at three California virtual schools in traditional school districts.  An analysis of the findings revealed that sites perceived the establishing founder, preliminary research, district support, teacher and staff selection, financial evaluation, and curriculum decisions as keys to the founding process.  The analysis also led to surprising conclusions, including the need for virtual schools to constantly change and adapt and the focus in this study of organizations over technology.  The findings have implications for traditional districts starting virtual schools. The study also indicates that changes in policy could reduce the need for organizational adaptation among virtual schools in traditional school districts.